New insights into the last deglaciation of the south-eastern flank of the Scandinavian Ice Sheet - Bitinas, Albertas (Quaternary Science Reviews, 2012)
The existing glaciodynamic paradigm used to explain the dynamics, morphogenesis, and deglaciation of the last Scandinavian Ice Sheet (SIS) does not satisfactorily reflect all the nuances of ice sheet dynamics, formation of particular forms of glacial relief, and details of deglaciation. Significant problems are to be found in the explanations proposed for the processes of deglaciation. Therefore a new theory for the deglaciation of the last SIS, based on new geochronological, geological, and geomorphological data has been developed and is presented here. It is suggested that along the south-eastern perimeter of the SIS, with the exception of the Salpausselkä moraine ridges, there is no evidence anywhere for re-advances of the SIS during deglaciation. Apart from the Salpausselkä moraine ridges the evidence for so-called ‘stadial’ or ‘phasial’ recessional events is interpreted as the result of SIS surges that occurred at different times and positions along the ice sheet margin. This new theory also proposes that deglaciation of the south-eastern flank of the SIS was dominated by surface thinning rather than marginal retreat. Characteristic landforms such as kame terraces located on the distal slopes of recessional marginal ridges and plateau-like glaciolacustrine kames, were developed during deglaciation probably due to the interaction of active ice lobes (surges) and masses of dead ice that persisting beyond the ice margin.